Research of the Patent Map of Harmonic Reducer - Chen Zhilan; Chen Wei (Jixie chuandong)
By using IPC classification method and data collection,the patent information hiding in the technological field of the harmonic reducer is mined. The corresponding patent map is drawn,the issues related to research harmonic reducer technology in the global scope of the patent layout,key technology and research focus are studied. The technology industry development trend,key technology areas and competition mechanisms are analyzed,the development present situation and future development trend in the field of technology are obtained.